Illuminating Jesus in the Middle Ages
1 online resource.
Keywords: In Illuminating Jesus in the Middle Ages, editor Jane Beal and other scholars analyse the reception history of images and ideas about Jesus in medieval cultures (6th–15th c.). They consider representations of Jesus in the liturgy of the medieval church, Psalters and psalm commentaries, bestiaries, the Glossa ordinaria, and Middle English vitae Christi as well as among the English, the Irish, and Europeans, adherents to the cult of the Holy Name, participants in the Feast of Corpus Christi, and medieval contemplatives, including Bede, Theophylact of Ochrid, Saint Francis, Gertrude the Great, Dante, Julian of Norwich, and medieval English and European visionaries, among others. Contributors are Jane Beal, George Hardin Brown, Aaron Canty, Tomás Ó Cathasaigh, Thomas Cattoi, Andrew Galloway, Julia Bolton Holloway, Michael Kuczynski, Rob Lutton, Vittorio Montemaggi, Paul Patterson, Linda Stone, Lesley Sullivan Marcantonio, Larry Swain, Donna Trembinski, Nancy van Deusen, and Barbara Zimbalist.